Comparison of Paleo-Mahakam Delta with Other Delta Systems - F. Hasan Sidi (Ikatan Ahli Geologi Indonesia, 1999)
The Middle to Upper Miocene delta system in Kutai Basin is compared with several published delta models in this article. The modern day Mississippi has been taken to represent fluvial-dominated deltas, Colorado delta in the Gulf of California for tide-dominated delta, and the Rhone delta for the wave-influenced comparison.